Ratio of ForageâConcentrate that Contain Fermented Tapioca by Product and Pollard and its Effect on Conjugated Linoleic Acid and Rumen Fermentation Parameters - Suryapratama, W (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
An experiment has been conducted to investigate the ratio of forage â concentrate that contain tapioca by product and pollard as fermented by Saccharomyces cerevisiae on conjugated linoleic acid and rumen fermentation parameters.Â In vitro experiment with Completely Randomized Block Design was performed with six periods of collecting rumen fluid as block.Â The rumen fluid was collected from fistulae cow in Animal Science Experimental Farm, University of Jenderal Soedirman. The diet consists of elephant grass as forages and concentrate that contain 45% of tapioca by product and pollard (ratio 1:1), urea added, then fermented with Saccharomyces cereviciae.Â Another 55% of the concentrate contain of rice meal, coconut meal, soybean oil, mineral and salt.Â Â Treatments were ratio of forage to concentrate i.e. 60:40; 70:30 and 80:20.Â Therefore 18 experimental units exist.Â Variables measured were VFA, N-NH3, conjugated linoleic acid concentration and protein synthesis of ruminal microorganism.Â Analysis of variance with orthogonal polynomial resulted that the ratio of forage-concentrate has significant effect on VFA concentrationÂ (P<0.05), N-NH3 and protein synthesis of ruminal microorganism (P<0.01). As forage increase, the VFA, N-NH3 and CLA linearly increase, but protein synthesis of ruminal microorganism linearly decrease.Â The highest of CLA obtained in diet with forage- concentrate ratio 80:20. (Animal Production 7(3): 142-149 (2005)Â Key Words: VFA, N-NH3, Microbial Protein, Linoleic, CLA, Ratio Forage-Concentrate